PNEUMONIA IN CAMEL Globule Leukecytes and Mast Cells in Bronchopulmonary system of Camel with Natural Parasitio Infection. - S. Mahmoud, G.; M. Mahmoud, M.; M. Shakir., M. (The Iraqi Journal of Veterinary Medicine, 1990)
The globule leukecytes and mast cells were detected in the respiratory tract of camel with natural parasitic infection, while these cells were absent in non parasitised lungs of camels. Histochemical investigations revealed cytochemical similarities between the globule leukecytes and mast cells of camel respiratory tract. Their granules contained s sulphated acidmucopolysaccharide associated with basic protein.